O Colégio São Benedito e a escolarização da população negra em Campinas-SP no início do século XX - Sgarbosa, Lívia (2018)
In the post-abolition period and in the First Republic, the black population was removed from the minimum conditions to integrate into Brazilian society, which underwent major transformations with the goal of developing the nation. There was a great enthusiasm for education, considered as redemptive and capable of removing Brazil from the situation of backwardness caused by the long period of colonial slavery. Defending the expansion of schools and expanding the supply of places did not apply to blacks, who encountered many barriers to access to education. In this context, the Irmandade São Benedito began, at the end of the 19th century, in Campinas, the offer of education for the brothers and their children of the "men of color", seeking to fill the vacancies in public schools. With this work, we try to understand how the professor Francisco José de Oliveira constituted and maintained the functioning of the Colégio São Benedito in the period from 1902 to 1936 and the participation of the Colégio São Benedito and the performance of the black professors Francisco José de Oliveira and Benedito Evangelista in the process of emancipation of the black population of Campinas, in the post-abolition period, in the early twentieth century. The Colégio São Benedito closed its doors in 1936, and members found themselves drifting, but the struggle of the educators who were involved in this educational institution, lasted for decades, through a litigation process of reintegration of possession. The work then sought to understand these passages and actions of the educators, and was carried out through bibliographical and documentary research. The historical sources were searched in the Memory Center of UNICAMP (CMU), in the archives of the City Hall and Campinas City Council and in the collection of prof. Benedito Evangelista, with documents from the Colégio São Benedito.